Pseudohypoparathyroidism type 1B mimicking gitelman syndrome: diagnostic pitfalls and molecular insights - Zhao, Yiming; Mou, Lijun; Akaaboune, Oumayma; Zhang, Jiudan (Frontiers in Genetics, 2025)
ObjectivePseudohypoparathyroidism type 1B (PHP1B), caused by abnormal methylation of the GNAS gene leading to parathyroid hormone (PTH) resistance, lacks Albright hereditary osteodystrophy features and is often misdiagnosed. PHP1B and Gitelman syndrome (GS) share overlapping features, including hypokalemia, hypocalcemia, hypomagnesemia, and metabolic alkalosis, posing challenges in clinical differentiation. This study aimed to explore the clinical characteristics, diagnostic strategies, and therapeutic responses of PHP1B presenting with hypokalemia and to explicitly address the diagnostic challenge of differentiating it from GS.MethodsRetrospective analysis of five patients initially misdiagnosed with GS due to hypokalemia but ultimately confirmed as PHP1B were collected. Whole-exome sequencing (WES) was used to exclude mutations in genes associated with renal tubular diseases, and methylation-sensitive multiplex ligation-dependent probe amplification (MS-MLPA) was employed to assess GNAS methylation status.ResultsPatients (median age 48 years; 60% female) had prolonged diagnostic delays (median 11 years). Universal clinical manifestations included muscle cramps and weakness. Biochemical profiling revealed hypokalemia (mean potassium 3.14 mmol/L), hypocalcemia (mean calcium 1.55 mmol/L), and elevated PTH (mean 422.1 pg/mL). All patients exhibited intracranial calcifications, predominantly in the basal ganglia. Genetic testing excluded Bartter/Gitelman syndromes, while MS-MLPA identified multi-differentially methylated region defects (NESP hypermethylation with AS1/XL/A/B hypomethylation) in four patients and isolated A/B hypomethylation with heterozygous STX16 deletion in case 5. Electrolyte levels improved with calcium, calcitriol, and potassium supplementation, though two patients required long-term potassium maintenance.ConclusionPHP1B can present with nonspecific hypokalemia, mimicking GS. Definitive diagnosis requires combined WES and methylation analysis, particularly in WES-negative cases with PTH resistance and intracranial calcifications. Therapeutic focus should prioritize calcium/calcitriol over potassium supplementation, with epigenetic heterogeneity guiding long-term management.